Beam exchange of a circulator cooler ring with an ultrafast harmonic kicker - Park, Gunn Tae; Guo, Jiquan; Rimmer, Robert A.; Wang, Haipeng; Wang, Shaoheng (Physical review. Accelerators and beams, 2021)
In this paper, we describe a harmonic kicker system used in the beam exchange scheme for the circulator cooling ring (CCR) of the Jefferson Lab Electron-Ion Collider. By delivering an ultrafast deflecting kick, a kicker directs electron bunches selectively in/out of the CCR without degrading the beam dynamics of the CCR optimized for ion-beam cooling. We will discuss the design principle of the kicker system and demonstrate its performance with various numerical simulations. In particular, the degrading effects of realistic harmonic kicks on the beam dynamics, such as 3D kick field profiles interacting with the magnetized beam, are studied in detail with a scheme that keeps the cooling efficiency within allowable limits.